Antioxidant activity of pumpkin leaf extract(Cucurbita moschata duch.) Using the dpph method - Risa Supriningrum; Miftahul Nabila Khusnah; Supomo Supomo (Jurnal Riset Kefarmasian Indonesia, 2026)
Pumpkin leaves (Cucurbita moschata Duch.) have benefits as an antidiabetic agent, stomach protector, and can increase blood hemoglobin levels, thereby treating anemia. Pumpkin leaves contain vitamin A, vitamin B, carbohydrates, phosphorus, calcium, iron, vitamin C, and secondary metabolites that have antioxidant potential. The purpose of this study was to determine the antioxidant activity of yellow pumpkin leaf extract using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The research stages included plant identification, simplisia preparation, extraction by maceration with 95% ethanol solvent, phytochemical screening, and testing of antioxidant activity with DPPH free radicals and vitamin C as a comparison. The results of the antioxidant activity test of the ethanol extract of pumpkin leaves showed very strong antioxidant activity with an IC50 value of 24.29 ppm, and a vitamin C IC50 value as a comparison of 9.809 ppm.